A justiça desportiva e a mitigação do princípio da inafastabilidade da jurisdição - Varalli, Riccardo Marcori (2020)
It´s a work in which Sports Justice and the mitigation of the principle of non-avoidability of the Jurisdiction is discussed. Both, the principle and Sports Justice are provided in the Federal Constitution and there must be harmony in the application of them. We will approach, therefore, the historical evolution of Sports Law in Brazil, making a contextual analysis, as well as the principles related to the theme. The structure, performance and organization of Sports Justice is demonstrated. There is an apparent clash between Sports Justice and Common Justice, given the principle of jurisdictional non-avoidability, which, as we intend to demonstrate, is apparent, since it must be mitigated in view of the specialty of Sports Justice